2014
DOI: 10.1016/j.ypmed.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a 12-month randomized clinical trial to increase physical activity in multiethnic postpartum women: Results from Hawaii's Nā Mikimiki Project

Abstract: Objective Few postpartum ethnic minority women perform leisure-time moderate-to-vigorous physical activity (MVPA). The study tested the effectiveness of a 12-month tailored intervention to increase MVPA in women with infants 2–12 months old. Methods From 2008–2011, women (n=311) with infants (average age = 5.7 months) from Honolulu, Hawaii were randomly assigned to receive tailored telephone calls and access to a mom-centric website (n=154) or access to a standard PA website (n=157). MVPA was measured at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(106 citation statements)
references
References 83 publications
1
102
0
2
Order By: Relevance
“…Two comparable randomized technology trials of physical activity with mothers that incorporated technology found statistically significant increases in MVPA minutes in the range of the increases we found in inactive women [48,51]. One trial found an increase of 92 MVPA minutes per week for mothers of babies 3+ months comparable to our difference of 51 MVPA minutes per week using the vigorous enhanced equation; and a second trial found an increase of 49 MVPA minutes per week comparable to our difference of 33 MVPA minutes per week using the simple equation.…”
Section: Effectivenesssupporting
confidence: 54%
See 3 more Smart Citations
“…Two comparable randomized technology trials of physical activity with mothers that incorporated technology found statistically significant increases in MVPA minutes in the range of the increases we found in inactive women [48,51]. One trial found an increase of 92 MVPA minutes per week for mothers of babies 3+ months comparable to our difference of 51 MVPA minutes per week using the vigorous enhanced equation; and a second trial found an increase of 49 MVPA minutes per week comparable to our difference of 33 MVPA minutes per week using the simple equation.…”
Section: Effectivenesssupporting
confidence: 54%
“…Many physical activity trials for mothers require fairly high time commitments from participants, primarily through coaching and education in person [14,[45][46][47], remotely via telephone and texts [48,49], or both [50][51][52]. Participants' time in this study went almost entirely towards exercising.…”
Section: Feasibility and Acceptabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Full-text publications were obtained of the resulting 20 articles. 9 of them were excluded due to the following reasons: different population group (pregnant women without hypertensive disorders or postpartum women) [76][77][78]; other disorders (gestational diabetes mellitus) [79], [80]; the same m-Health solution [81][82][83][84]. Finally, data extraction was performed on the final 11 included articles.…”
Section: Resultsmentioning
confidence: 99%